2018
DOI: 10.1039/c7fo01787a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calorie restriction plus fish oil supplementation on abnormal metabolic characteristics and the iron status of middle-aged obese women

Abstract: The increasing prevalence of obesity and sedentary lifestyles has led to a higher incidence of metabolic syndrome (MetS) worldwide as well as in Taiwan. Middle-aged women are at a greater risk of MetS, type 2 diabetes, and cardiovascular disease than men because they have more subcutaneous fat and larger waist circumferences compared with men with equal visceral fat levels. In this study, we investigated the effects of calorie restriction (CR) and fish oil supplementation (CRF) on middle-aged Taiwanese women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In another study that involved patients with bipolar disorders, Holdemania at the genus level was also found to be negatively correlated with BMI (Hu et al, 2019 ). Another study showed that the abundance of Ruminococcaceae increased in obesity patients (Chávez-Carbajal et al, 2019 ), and Ruminococcaceae was associated with antidepressant effects in rats under chronic mild stress (Tung et al, 2019 ). Moreover, the increased levels of Ruminococcaceae would decrease after weight reduction (Kang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In another study that involved patients with bipolar disorders, Holdemania at the genus level was also found to be negatively correlated with BMI (Hu et al, 2019 ). Another study showed that the abundance of Ruminococcaceae increased in obesity patients (Chávez-Carbajal et al, 2019 ), and Ruminococcaceae was associated with antidepressant effects in rats under chronic mild stress (Tung et al, 2019 ). Moreover, the increased levels of Ruminococcaceae would decrease after weight reduction (Kang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, DR studies tend to focus on improvements in health outcomes rather than lifespan extension due to the obvious limitations in assessing this metric. As with preclinical models, studies of DR in humans either find no sex differences, do not include sex differences as an experimental outcome [5,6], or include only one sex seeking an answer to a specific experimental question [7]. A recent study in non-obese humans suggests that a two-year 25% CR regimen is feasible in non-obese humans; the only sex differences observed were a slightly lower BMI in the cohort that was predominantly women (69.7%) [6].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between IL‐6 and hepcidin is well established. The literature showed that IL‐6 triggers hepcidin synthesis via signal transducer and activator of transcription 3‐dependent pathways, and downregulation of hepcidin by treatment with an anti‐IL‐6 receptor antibody improved anemia of inflammation . FO or the n‐3/n‐6 fatty acid ratio has potent anti‐inflammation effects, and a human study showed that the addition of FO suppressed IL‐6 synthesis by white blood cells .…”
Section: Discussionmentioning
confidence: 99%
“…Fish oil (FO) or n‐3 long chain PUFA supplementation was shown to reduce inflammation and the risk of MetS . However, the effects of FO on weight loss and the body composition are still uncertain .…”
Section: Introductionmentioning
confidence: 99%